Acute Pancreatitis Induced by Methimazole in a Patient With Subclinical Hyperthyroidism. (23rd June 2015) - Agito, Katrina; Manni, Andrea
We report here a unique case of methimazole (MMI)-induced pancreatitis. To our knowledge, this is the sixth case reported in the literature and the first diagnosed in a patient with toxic multinodular goiter. A 51-year-old Caucasian female with a history of benign multinodular goiter and subclinical hyperthyroidism was started on MMI 10 mg orally daily. Three weeks later, she developed sharp epigastric pain, diarrhea, lack of appetite, and fever. Her lipase was elevated 5 times the upper limit of normal, consistent with acute pancreatitis. There was no history of hypertriglyceridemia, or alcohol abuse. Abdominal computed tomography was consistent with acute uncomplicated pancreatitis, without evidence of gallstones or tumors. MMI was discontinued, and her hyperthyroid symptoms were managed with propranolol. Her acute episode of pancreatitis quickly resolved clinically and biochemically. One year later, she redeveloped mild clinical symptoms of hyperthyroidism with biochemical evidence of subclinical hyperthyroidism. MMI 10 mg orally daily was restarted. Five days later, she experienced progressive abdominal discomfort. Her lipase was elevated 12 times the upper limit of normal, and the abdominal computed tomography was again compatible with acute uncomplicated pancreatitis. MMI was again discontinued, which was followed by rapid resolution of her pancreatitis. The patient is currently considering undergoing definitive therapy with radioactive iodine ablation. Our case as well as previous case reports in the literature should raise awareness about the possibility of pancreatitis in subjects treated with MMI in the presence of suggestive symptoms. If the diagnosis is confirmed by elevated pancreatic enzymes, the drug should be discontinued.